Influence of humidity on moving away of TiCl2 from salt fusion at the electrolysis of MgCl2 - Бачурский, Денис Васильевич (Technology audit and production reserves, 2013)
The results of the study of the effect of titanium chloride during the electrolysis of molten magnesium chloride after reduction of titanium chloride are given. It was found that the humidity of molten chlorides has a significant effect on the removal of titanium from the melt. The results of processing the results of experiments allowed the building of regression equation. It is shown that moisture in the salt has a significant effect on cleaning the electrolyte from titanium impurities. Analysis of the results of experiments of the content of magnesium oxide showed that it does not exceed 0.05% by weight that is an indirect proof of reactions between magnesium oxide and titanium compounds. To effectively remove the titanium compounds from the molten salt it is proposed to load the moistened salt in the head unit of production line or in a separate working electrolyzer during the filling of the next portion of magnesium chloride.